Combinatorial Optimization of Metal‐Insulator‐Insulator‐Metal (MIIM) Diodes With Thickness‐Gradient Films via Spatial Atomic Layer Deposition - Abdullah H. Alshehri; Hatameh Asgarimoghaddam; Louis‐Vincent Delumeau; Viet Huong Nguyen; AlRasheed Ali; Mutabe Aljaghtham; Ali Alamry; Dogu Ozyigit; Mustafa Yavuz; Kevin P. Musselman (Advanced Electronic Materials)
Abstract Metal‐insulator‐insulator‐metal (MIIM) diodes with thickness‐gradient films for the insulator layers are fabricated for the first time. Spatially varying atmospheric‐pressure chemical vapor deposition is used to deposit ZnO and Al2O3 films with orthogonal gradient directions, producing 414 MIIM diodes with 414 different ZnO/Al2O3 film‐thickness combinations on a single substrate for combinatorial and high‐throughput optimization. The nm‐scale ZnO/Al2O3 films are printed in only 2 min and the entire device fabrication takes 7 h, which is much less than conventional approaches for investigating many insulator‐thickness combinations. Rapid identification of the optimal thickness combination is demonstrated; high‐performance diodes (asymmetry = 227, nonlinearity = 13.1, and responsivity = 12 A/W) are observed when a trap‐assisted tunneling mechanism is dominant for insulator thicknesses of 3.4–4.4 nm (ZnO) and 7.4 nm (Al2O3).